2017
DOI: 10.1016/j.bbadis.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1R signalling contributes to IL-6 production and T cell dependent inflammation in rheumatoid arthritis

Abstract: IGF-1R signalling contributes to T cell dependent inflammation in arthritis. Inhibition of IGF-1R on the level of insulin receptor substrates alleviates arthritis by restricting IL6-dependent formation of Th17 cells and may open for new treatment strategies in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 85 publications
7
39
0
Order By: Relevance
“…This observation reveals that TXNDC5 can up-regulate IL-6 levels by suppressing IGFBP1 expression. IGF-1 receptor signalling was shown recently to contribute to IL-6 production in RA [36], which supports our findings. The IL-6 inhibitor, tocilizumab, a humanized anti-IL-6 receptor monoclonal antibody, shows outstanding efficacy in RA [34,35].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation reveals that TXNDC5 can up-regulate IL-6 levels by suppressing IGFBP1 expression. IGF-1 receptor signalling was shown recently to contribute to IL-6 production in RA [36], which supports our findings. The IL-6 inhibitor, tocilizumab, a humanized anti-IL-6 receptor monoclonal antibody, shows outstanding efficacy in RA [34,35].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, we suggest that TXNDC5 decreases IL-6 production rather than the production of other cytokines by regulating IGFBP1 expression. IGF-1 receptor signalling was shown recently to contribute to IL-6 production in RA [36], which supports our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Under physiological conditions, these two signaling pathways operate independently and mediate respectively metabolic and antibacterial functions. Under inflammatory conditions created by obesity and RA, activation of IGF1R and TLR4 synergize to trigger adaptive immune responses and T cell differentiation in the target adipose and synovial tissues [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RA is a self-maintaining inflammatory disease, in which the destruction of the adjacent bone is induced by inflammation ( 33 ). Studies have demonstrated that inflammatory cytokines, including IL-1β, IL-6, IL-8, MMP-1 and MMP-13, serve a key role in the pathogenesis of RA ( 34 , 35 ). The results of the present study indicated that inhibition of miR-143-3p significantly inhibited the production of these inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the present study indicated that IGF1R and IGFBP5 are target genes of miR-143-3p. It has been reported that IGF-1R signaling contributes to T cell-dependent inflammation in RA ( 35 ). Furthermore, it has been suggested that MMP-13 and IGFBP5 are important factors that mediate the development of OA ( 36 ).…”
Section: Discussionmentioning
confidence: 99%